Development of a prototype mechanically moveable and height-adjustable ladder / Muhammad Aiman Mat Nawi and Miqdad Khairulmaini - Mat Nawi, Muhammad Aiman; Khairulmaini, Miqdad (School of Mechanical Engineering, 2023)
The Mechanically Moveable and Height-Adjustable Ladder (MeMoHAL) is an innovative product that aims to save costs by combining two features in one ladder. The problem statement for this project is the need for a ladder that is both mechanically moveable and height-adjustable without having to purchase two separate ladders. The objective of this project is to create a cost-effective ladder that meets both these requirements. The methodology involves the design and implementation of the ladder with moveable and adjustable features. The results obtained from the product show that MeMoHAL is a viable solution to the problem, with advantages such as cost-saving, convenience, and ease of use. The significance of this project lies in the potential for commercial success of the MeMoHAL in the market. This innovative ladder not only saves costs, but also provides a practical solution for users who need both moveable and adjustable features in one ladder. In conclusion, this project presents an efficient solution to the problem of purchasing two different ladders for different features